The baking merits of winter rye - E. N. Shabolkina; N. V. Anisimkina (Зерновое хозяйство России, 2018)
Rye is considered to be the second bread as it’s both tasty and useful. At present, a healthy lifestyle and in particular proper nutrition are preferable, thus the consumption of bread baked from pure rye flour or from its mixture with wheat flour (with a greater share of rye flour) increases. Taking into consideration that rye is used for nutrition, the purpose of our research is to study biochemical, technological traits of quality of the present varieties of winter rye and to estimate baking merits of rye and rye-wheat bread. The study has been carried out on the experimental plots of the Samara RIA. Seven varieties of winter rye ‘Bezenchukskaya 87’ (standard), ‘Olga’, ‘Roksana’, ‘Antares’, ‘Bezenchukskaya 110’ and the line ‘GK-80’ have been taken as the experimental material in 2016. In dry summer of 2016 all studied varieties of winter wheat produced the grain with a low amylolytic enzyme activity (the ‘falling number’ determined according to Hagberg-Perten was 271-368 s), with a maximum viscosity (700-1000 e.am.) and can be uses as the improvers in the mixtures with rye flour of poor quality or in the mixture with wheat flour. All studied varieties of winter rye showed a large bread volume in the experimental baking with the maximum bread volume of 515-575 cm3 per 100 g of flour (the varieties ‘Bezenchukskaya 87’ and ‘Roksana’) and the minimum 470-480 cm3. The wheat flour added to the rye flour has a positive effect on such rheological traits as dough extension and bread volume. Bread baked directly from the mixture of rye and wheat flour (1:1) according to the technology of State Committee with an intensive dough kneading was of light color with good porosity, with slightly sweet taste and with good appearance